Somebody like you : a novel - Vogt, Beth K. (Howard Books, 2014)
"In this beautifully rendered, affecting novel, a young widow's world is shattered when she meets her late husband's identical twin--and finds herself caught between honoring her husband's memory and falling in love with his reflection" --